Dual-edge triggered storage elements and clocking strategy for low-power systems. - Nedovic, N. (IEEE Transactions on VLSI systems)
This paper describes the classification, detailed timing characterization, evaluation, and design of the dual-edge triggered storage elements (DETSE). The performance and power characterization of DETSE includes the effect of clocking at halved clock frequency and impact of load imposed by the storage element to the clock distribution network. The presented analysis estimates the timing penalty and power savings of a system based on DETSE, and gives design guidelines for high-performance and low-power application. In addition, the paper presents a class of dual-edge triggered flip-flops with clock load, delay, and internal power consumption comparable to the fastest single-edge triggered storage elements (SETSE). Our simulated results show that by halving the clock frequency, dual-edge clocking strategy can save about 50% of the power consumed by the clock distribution network, and relax the design of clock distribution system, while paying virtually no penalty in throughput.